Alkaloid content variability in the seeds of narrow-leafed lupine accessions from the VIR collection under the conditions of the Russian Northwest - M. A. Vishnyakova; A. V. Salikova; T. V. Shelenga; G. P. Egorova; L. Yu. Novikova (Вавиловский журнал генетики и селекции)
Alkaloid content was assessed in the seeds of 59 narrow-leafed lupine (Lupinus angustifolius L.) accessions from the VIR collection in the environments of Leningrad Province. The selected set included accessions of different statuses (wild forms, landraces, and advanced cultivars) and different years of introduction to the collection. Alkaloids were analyzed using gas-liquid chromatography coupled with mass spectrometry. Concentrations of main alkaloids: lupanine, 13-hydroxylupanine, sparteine, angustifoline and isolupanine, and their total content were measured. The total alkaloid content variability identified in the seeds of the studied set of accessions was 0.0015 to 2.017 %. In most cases, the value of the character corresponded to the accession’s status: modern improved cultivars, with the exception of green manure ones, entered the group with the range of 0.0015–0.052 %, while landraces and wild forms showed values from 0.057 to 2.17 %. It is meaningful that the second group mainly included accessions that came to the collection before the 1950s, i. e., before the times when low-alkaloid cultivars were intensively developed. Strong variability of the character across the years was observed in the accessions grown under the same soil and climate conditions in both years. In 2019, the average content of alkaloids in the sampled set was 1.9 times higher than in 2020. An analysis of weather conditions suggested that the decrease in alkaloid content occurred due to a significant increase in total rainfall in 2020. Searching for links between the content of alkaloids and the type of pod (spontaneously non-dehiscent, or cultivated, spontaneously dehiscent, or wild, and intermediate) showed a tendency towards higher (approximately twofold in both years of research) total alkaloid content in the accessions with the wild pod type and the nearest intermediate one compared to those with the pod non-dehiscent without threshing. The correlation between the average total alkaloid content and seed color, reduced to three categories (dark, or wild, light, or cultivated, and intermediate), was significantly stronger in the group with dark seeds (5.2 times in 2019, and 3.7 times in 2020). There were no significant differences in the percentage of individual alkaloids within the total amount either between the years of research or among the groups with different pod types or the groups with different seed coat colors.